Multi-literacies in the 21st century and the role of the print-based text in public education - Dixon, Michael S., author; Coke, Pamela K., advisor; Mallette, Dawn M., committee member; Reid, Louann, committee member (Colorado State University. Libraries, 2010)
This study examines the appeal of print-based and multimodal-based texts in relation to the 21st century learner and in context of the modern secondary level public education classroom. A review of literature gives depth to the ways in which print-based and multimodal-based texts have established themselves within the institution of education as well as how each type of text relates to the fields of semiotic systems and technology. The aim of the study is to examine and measure the appeal of print-based and multimodal-based texts to the 21st century learner. To achieve this goal, two types of research provided results: a quantitative classroom study in which students engaged and interacted with a print-based assessment and a multimodal-based assessment and provided feedback via a survey, and a qualitative study in which educators provided their thoughts and opinions on the role of print-based and multimodal-based texts at the secondary level of education via an electronic questionnaire.
Department Head: Bruce A. Ronda.